Effects of lifestyle changes on adults with prediabetes: A systematic review and meta-analysis. Issue 5 (October 2018) - Glechner, Anna; Keuchel, Lina; Affengruber, Lisa; Titscher, Viktoria; Sommer, Isolde; Matyas, Nina; Wagner, Gernot; Kien, Christina; Klerings, Irma; Gartlehner, Gerald
Highlights: Lifestyle intervention lowers type 2 diabetes risk in people with prediabetes. Weight loss is commonly achieved but there is great variation between studies. The majority of studies concluded that lifestyle intervention is cost-effective. Lifestyle intervention is most cost-effective over a lifelong analysis period. More research is necessary to compare different types of lifestyle intervention. Abstract: Aims: To assess the efficacy, safety, and cost-effectiveness of lifestyle intervention, compared with treatment as usual in people with prediabetes as defined by the American Diabetes Association. For older studies, we used the 1985 World Health Organization definition. Methods: We systematically searched multiple electronic databases and referenced lists of pertinent review articles from January 1980 through November 2015. We performed an update search in MEDLINE on April 26, 2017. Based on a priori established eligibility criteria, we dually reviewed the literature, extracted data, and rated the risk of bias of included studies with validated checklists. To assess the efficacy of lifestyle intervention to prevent or delay further progression to type 2 diabetes, we conducted a random-effects meta-analysis. We assessed the certainty of evidence using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Result: Pooled results of 16 randomized controlled trials showed that people with prediabetes who received lifestyle intervention had a lower rate of progression to type 2 diabetes after one (4% vs. 10%, RR 0.46 [CI 0.32, 0.66]) and three years of follow-up (14% vs. 23%, RR 0.64 [95% CI 0.53, 0.77]). The majority of the studies also showed a greater weight loss in lifestyle intervention participants, with a great variation between studies. Costs per quality-adjusted life-year were lower when the benefits of lifestyle intervention were analyzed over a lifelong time horizon compared to only the period of lifestyle intervention (three years) or to modeling over a ten-year period. Conclusion: Lifestyle intervention is an efficacious, safe, and cost-effective measure to reduce the risk of progression to type 2 diabetes in people diagnosed with prediabetes. More research is necessary to compare the efficacy of various modes, frequencies, and intensities of lifestyle intervention across studies.